Analyzing the Impact of Social Media on Student Discipline Levels: A Study of Civic Education Students at Universitas Halu Oleo - Syahbudin, Syahbudin; Hasanah, Nur; Astarin, Wa Ode Syamzahrah (FKIP Universitas Lampung, 2024)
Social media plays a central role in students’ daily routines, significantly impacting their academic achievements and personal discipline. Objective: This research focuses on exploring the connection between social media usage and discipline levels among Civic Education Department (PPkN) students at FKIP, Halu Oleo University. Methods: Adopting a quantitative survey approach, the study gathered data through an online questionnaire targeting a population of 118 students from the 2023 cohort. Utilizing purposive sampling, a sample size of 91 students was analyzed. The data were processed with simple linear regression to assess the influence of social media on discipline. Findings: The findings revealed a notable link between social media usage and students’ discipline, evidenced by a hypothesis test result of 0.00 < 0.05. Furthermore, the R Square value demonstrated that 19.6% of variations in student discipline levels could be attributed to their social media usage. Conclusion: These insights underscore the importance of mindful social media use among students. To promote a balanced approach, educators and parents should actively guide and educate students on the responsible and productive use of social media. Such efforts can help students harmonize their academic pursuits with social engagements while minimizing potential downsides. This study sheds light on the influential role of social media in shaping student behavior and provides actionable recommendations for fostering effective time management and enhanced productivity.Keywords: social media, student discipline, parents, academics.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024133